Features of optical properties of high stable CdTe photovoltaic absorber layer - Yavorskyi, R.S. (Physics and Chemistry of Solid State, 2020)
In this paper, the technology of obtaining and effect of annealing on the morphology and optical properties of cadmium telluride thin films has been investigated. The effect of vacuum chamber modes on the growth of thin films has been studied. For obtained cadmium telluride thin films were used a modified thermal evaporation method deposited by Physical Vapor Deposition technique on a glass substrate with different thicknesses. The transmission measurements were carried with UV-ViS-NIR Spectrophotometer in the wavelength range 180-3300 nm, to analyze the optical properties as a function of wavelength. The optical band gap values were 1.49 eV for as-grown films and 1.46 eV after annealing. The refractive indexes of the samples were defined in the range of 2.6 – 2.8 for as-grown films and the indexes have increased after annealing depending on the wavelength region and film thickness. After annealing, the coalescence mode of growth is observed.